2004
DOI: 10.1167/iovs.04-0455
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Hepatocyte Growth Factor against Photoreceptor Degeneration in Rats

Abstract: Intravitreal HGF led to the morphologic and physiological preservation of photoreceptors in rats with photoreceptor degeneration induced by phototoxicity or a gene mutation. The antiapoptotic effect may be the mechanism for the neuroprotective action of HGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
1
19
0
4
Order By: Relevance
“…According to the results from previous experiments, there are several lines of evidence that the death of photoreceptors can be delayed with cytokines, neurotrophic or neuroprotective factors [29][30][31][32][33][34][35][36][37][38][39]. To this end, apoptotic cascades can be blocked either directly through receptor-mediated signalling, typical for neurotrophic factor or growth factors [40], or indirectly through molecules produced by glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results from previous experiments, there are several lines of evidence that the death of photoreceptors can be delayed with cytokines, neurotrophic or neuroprotective factors [29][30][31][32][33][34][35][36][37][38][39]. To this end, apoptotic cascades can be blocked either directly through receptor-mediated signalling, typical for neurotrophic factor or growth factors [40], or indirectly through molecules produced by glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 In these studies, treatment resulted in b-wave thresholds being preserved to a far greater degree than maximum b-wave amplitudes. For instance, differences between the treated eyes and nontreated eyes were 2.76 and 0.83 log units for the threshold and maximum amplitude, respectively.…”
Section: Implications In Studies Evaluating Treatment Effi Cacymentioning
confidence: 91%
“…Therefore, the b-wave has also been used as a functional measure of treatment effi cacy in studies using dystrophic RCS rats. [11][12][13] It has recently been reported that the third-order neuron response participates more than expected in shaping the ERG in both the normal and diseased retina. Bush and colleagues demonstrated that the scotopic threshold response (STR) 14 generated by the inner retina 15,16 was less affected than the scotopic b-wave by photoreceptor degeneration in aged dystrophic RCS rats.…”
mentioning
confidence: 99%
“…We and others have shown that PI3K activation is neuroprotective [27,28]. Hepatocyte growth factor (HGF) is shown to protect light-induced photoreceptor degeneration [29] and retinal ischemia-reperfusion injury [30] and also attenuates the ceramide-induced apoptosis in retina [31]. All these studies clearly suggest that HGF possesses both neuroprotective and anti-oxidant properties [29,31]; however, the molecular mechanism behind the neuroprotective effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%